Venous Saturation Monitoring in Anesthesiology and Intensive Care - A. A. Smetkin; M. Yu. Kirov (Общая реаниматология, 2008)
The review describes the problem of adequacy of oxygen transport and the ability of its assessment using the venous oxygen saturation monitoring. The paper contains physiological basics and principles of venous oxygen saturation monitoring as well as current data regarding the efficacy of such monitoring in different fields of critical care medicine. Key words: oxygen transport, venous oxygen saturation, oxygen delivery.